Ferrites gas sensors: A Review - Shedam, Rakesh M.; Kashid, Priyanka P.; Mathad, Shridhar N.; Deshmukh, Rahul B.; Shedam, Mahadev R.; Gadkari, Ashok B. (Physics and Chemistry of Solid State, 2022)
Gas sensors that are highly sensitive, stable, and selective are increasingly in demand to detect toxic gases. As a result of the need to monitor concentrations of these gases, humans, animals, and the environment are all protected. Metal ferrites (AFe2O3, where A is a metal) are a major factor in this field. The development of ferrite gas sensors has made remarkable advances in the detection of toxic gases from vehicle exhaust, biological hazards, environmental monitoring, and pollution monitoring over the last decade. It is important for ferrite gas sensors to consider parameters like phase formation, crystallite size, particle size, grain size, dopants, surface area, sensitivity, selectivity, operating temperature, gas concentration, response time, and recovery time. There are various materials for gas sensing use such as carbon monoxide (CO), carbon dioxide (CO2), methane (CH4), ethyl alcohol (C2H5OH), hydrogen sulfide (H2S), C2H5COOH, oxygen (O2), hydrogen (H2), chlorine (Cl2), NH3, C4H10, CH3COOH, gasoline, acetylene, petrol, and liquefied petroleum gas (LPG). Various methods are used to prepare ferrite gas sensors. Additionally, a brief description is provided of the various methods employed for synthesizing ferrite gas sensors. A comprehensive survey of ferrites as gas sensors, such as nickel, copper, zinc, cadmium, cobalt, magnesium, manganese, and multi-component ferrites, prepared by various methods.